2003
DOI: 10.1046/j.1365-2656.2003.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between temporal variability and persistence time in animal populations

Abstract: Summary 1.The relationship between temporal variability, spectral redness and population persistence for a large number of long-term time series was investigated. Although both intuition and theory suggest that more variability in population abundance would mean greater probability of extinction, previous empirical support for this view has not been conclusive. Possible reasons are the shortage of long-term data and the difficulties of adequately characterizing temporal variability, two issues that are explici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
229
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(237 citation statements)
references
References 52 publications
7
229
0
1
Order By: Relevance
“…We propose a class of surrogates that models the underlying statistical structure of the time series as 1/ƒ noise (Halley 1996). Such a model is rather convenient as it allows for the 'more time, more variation' effect displayed by many ecological time series (Lawton 1988, Inchausti & Halley 2002, Vasseur & Yodzis 2004. This class of surrogates is thus adapted to ecological time series, as it is, in addition, designed to deal with short time series.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…We propose a class of surrogates that models the underlying statistical structure of the time series as 1/ƒ noise (Halley 1996). Such a model is rather convenient as it allows for the 'more time, more variation' effect displayed by many ecological time series (Lawton 1988, Inchausti & Halley 2002, Vasseur & Yodzis 2004. This class of surrogates is thus adapted to ecological time series, as it is, in addition, designed to deal with short time series.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Many abiotic environmental variables, such as temperature, are temporally autocorrelated (often showing a reddened spectrum [2,3]). Biotic environmental variables, such as resource or prey abundance, are also likely to have coloured noise properties, as many time-series of population size exhibit temporal autocorrelation [4,5]. Demographic rates depend on the environmental conditions and consequently coloured environmental noise can cause demographic rates also to be temporally autocorrelated, which in turn can affect population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…cific differences in population variability (Pimm 1991;Ariño and Pimm 1995;Inchausti and Halley 2002), we must therefore obtain a proper understanding of how the separate effects of demographic and environmental stochasticity are related to demographic variation across species. Theoretical analyses have shown that knowledge of demographic stochasticity is especially important for fluctuations of small populations (May 1973;Leigh 1981;Lande 1998;Lande et al 2003) that often are of management concern.…”
mentioning
confidence: 99%